Defense related enzymes implicated in resistance and susceptibility to Rhizoctonia solani, the causal agent of sheath blight of rice - M M, Sindhu; Kumar, MK Prasanna; Jayashree, A; Chethana, BS; Nagaraja, A (ORYZA-An International Journal of Rice, 2024)
Plants have evolved various defense mechanisms to defend themselves from phytopathogens. Pathogenesis-related proteins are produced as part of the active defenses. In this work, changes in the activity of defense-related enzymes in rice in response to Rhizoctonia solani were examined at different time intervals viz., 0, 24, 48, and 72 h post inoculation (hpi), in late tillering tolerant and susceptible cultivars of rice. When the pathogen was induced, the activities of defense-related enzymes like chitinase, b-1,3-glucanase, peroxidase (PO), polyphenol oxidase (PPO), phenylalanine ammonia lyase (PAL), and total phenol content significantly increased in the tolerant cultivar (Tetep) compared to susceptible (KRH-4). Tetep showed increased chitinase activity up to 72 hpi, whereas KRH-4 showed no significant change up to 48 hpi but then increased activity at that time. When compared to the susceptible cultivar, tolerant Tetep had the maximum b-1-3 glucanase activity at 48 hpi. Tetep had an early induction of PAL with the highest activity at 24 hours compared to the control, but no proper trend was seen in susceptible cultivar. The early PO activity culminates in Tetep at 48 hpi. Tetep and KRH-4 both showed higher PPO enzyme activity at 48 hpi. In both the tolerant and susceptible cultivars, SOD activity steadily rose to 24 hpi and subsequently increased gradually up to 72 hpi. Tetep reported a higher total phenol concentration in the infected sheath samples than KRH-4 at 72 hpi. In this work, we looked at the biochemical methods for describing the defense-related enzymes against the sheath blight pathogen.